Assistance of the Bueka As-Sakinah towards Sharia savings and loan cooperatives (KSPPS) - Fitrian Aprilianto; Rahmad Hakim (Universitas Muhammadiyah Magelang, 2022)
This community service seeks to assist people grasp the notion of muamalah maaliyah by illustrating real-life examples of sharia financial transactions in sharia cooperatives. Identification is the first step in the service method, which is followed by workshops, focus group discussions, and mentorship. As a result of the service, cooperative management and supervisors have a better understanding of the notion of Sharia finance.